NUMERICAL MODELING OF PROCESSES OF MASS CARRY AT VACUUM AND PLASMA PROCESSING STEELS - I. A. Ivanov; I. V. Misnik; X. T. E. Karmazhi (Литьë и металлургия)
The basic principles and main results of numerical research on the basic of method of statistical test of the mass and power carry processes at forming vacuum-plasma coverings are discussed in the article.